PEREMPUAN SEBAGAI RAS TERKUAT DI MUKA BUMI: Kajian Tafsir Tematik dengan Pendekatan Feminis - Affandi, Abdullah; Nabiel, Muhammad (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2024)
This article explores the concept of women as "the strongest race on earth" through thematic interpretive studies with a feminist approach. By integrating various feminist perspectives and analysis of religious texts, this article seeks to reveal the potential power of women that is often hidden or ignored in various patriarchal narratives. This study includes analysis of verses from the Koran, hadith, as well as relevant classical and contemporary texts, to show that women have extraordinary capacities in various aspects of social, economic and spiritual life. This article also highlights how inclusive and progressive interpretations can empower women and change social paradigms about their roles and contributions Keywords: Tafsir, Ras Terkuat, Perempuan